Value Chain Analysis of Restaurant and Eatery Business at The F1 Powerboat Racing Event (F1H2O) Throught a DMAIC Perspective in Toba Regency - Naibaho, Uli Arta; Santoso, Sugeng (Dinasti Publisher, 2024)
Toba Regency is one of the Lake Toba regions hosting the prestigious F1 PowerBoat (F1H2O) competition held in Balige City, Napitupulu Harbor area. Restaurants and eateries have an important role in providing food and drinks to visitors so that they contribute to regional economic growth. This research analyzes the value chain of restaurants and restaurants in Toba Regency after the F1 PowerBoat event through the DMAIC perspective, thus enabling a deeper understanding of the value chain, the added value generated, and the factors that affect business performance. This type of research is qualitative descriptive explorative, data collection methods with observation, interviews, and documentation of 5 restaurants and eatery business actors as key informants and the Kemenkomarves team as supporting informants who coordinate directly with the event organizer, InJourney. Results can be proven from data analysis using Nvivo and processed research data. The results of data coding found the words value chain and added value as words that were widely conveyed by business actors. Visualization of increased visitor data through percentage and total visitor data, PSP Holiday Restaurant 3360 (200%), Labersa Restaurant 3570 (150%), Tepi Danau Restaurant 5600 (200%), Damar Toba Restaurant 3360 (150%) and Balige Beach Restaurant 1736 (150%). The increase in value added in the value chain is an improvised evaluation of restaurants and eatery business actors.